A review on methods for materials planning and control in healthcare organisations. (13th December 2021) - Alemsan, Najla; Tortorella, Guilherme Luz; Vergara, Alejandro Francisco Mac Cawley; Sawhney, Rapinder
This study aims at identifying the existing methods for materials planning and control applied in healthcare organisations. An extensive literature review was performed in the main databased based upon two research axes: 1) materials planning and control; 2) health services. Besides the content and bibliometric analysis, literature evidence was analysed from the perspective of two theoretical lenses: types of flow of value and complexity levels of hospital departments. Results from this review allowed the indication of two main research directions: 1) integration among methods for materials planning and control; 2) financial assessment of the implementation of materials planning and control methods in hospitals. The healthcare sector is highly important due to the criticality of it is quality, safety concerning patient care and the high cost involved in its operations. Furthermore, resources are usually limited, complicating its management.